ANALYSIS OF THE IMPLEMENTATION OF THE WASTE MANAGEMENT PROGRAM AT THE JAMBANGAN RECYCLING CENTER IN SURABAYA CITY: ANALISIS IMPLEMENTASI PROGRAM PENGELELOAAN SAMPAH DI PUSAT DAUR ULANG JAMBANGAN KOTA SURABAYA - Ammar Alfaini, Ahmad Faishal; Vira Pristikawati, Mela Dwi Novita Sari, Nur Aini Rosalia, Siradj Aqshal Raul Zaenal, (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The waste management program is a form of implementation of Surabaya City Regional Regulation Number 5 of 2014 concerning Waste Management and Cleanliness in the City of Surabaya. The aim of the waste management and environmental hygiene program is to improve the quality of life of the community through improving environmental health and cleanliness. The type of research used in this research is descriptive qualitative research. The focus of this study is to describe the Implementation of the Waste Management Program through the Jambangan PDU locus using the George Edward III model of public policy implementation. The results of this study are (1) the communication process is the provision of debriefing and training for waste management officers at the Jambangan PDU by the Surabaya City Environmental Service besides that routine meetings are also held every 6 months to find out the progress of PDU management which can be done by fast, easy and cheap through online. (2) There is integration between officers and the community such as KSH, RT, RW and residents around Jambangan. Then for (3) disposition, in waste processing at the Jambangan PDU namely the Surabaya City Environmental Service (DLH) as well as from Jambangan PDU supervisors and Jambangan PDU employees where the Surabaya City Environmental Service (DLH) serves as the coordinator responsible for all management implementation. In addition, there is community involvement in waste sorting but awareness in this sorting has not been carried out by the community as a whole. (4) Disposition in waste processing at the Jambangan PDU, namely weighing the waste, waste sorting process, pressing process for organic waste, cleaning the location so that cleanliness at the Jambangan PDU is maintained and comfortable.